ANALYSIS OF PASTORS' FAILURE IN EVANGELIZATION AND ITS CONSEQUENCES ON CONGRESS GROWTH - YUlian Anouw (Seminari Tinggi St. Fransiskus Xaverius Ambon, 2026)
Evangelization is the church's primary mandate in carrying out Christ's Great Commission, and plays a crucial role in the spiritual and quantitative growth of congregations. Pastors, as spiritual leaders, have a strategic responsibility to mobilize evangelism, both directly and through congregational empowerment. However, in practice, many churches experience stagnation or decline in membership due to the pastor's failure to carry out his evangelism function. This study aims to analyze the factors causing this failure and evaluate its impact on congregational growth. Using a qualitative approach through case studies of several churches in the Kingmi Classis Sorong Fakfak church area over the past 10 years, it was found that pastoral failure is influenced by a lack of missionary training, excessive administrative focus, and minimal social involvement. The consequences include a decline in the number of new members, a weakening of service enthusiasm, and a diminished church relevance in the community. This study recommends a renewed spiritual leadership strategy that is more missionary and contextual to encourage sustainable congregational growth.